Differences in perception of barriers in higher education and the completion of a degree among Latinos in the U.S. - Becerra, David, author (Colorado State University. Libraries, 2009)
Presented at the Society for Social Work and Research Conference, January 16, 2009, New Orleans, Louisiana.
Keywords: college degree; higher education; academic achievement; Latino students; barriers; school social work